Description and Dynamic Analyses of the 1935 Luchedu Rock Avalanche in Sichuan, China. (7th July 2022) - Cui, Jie; Gao, Chunyu; Zhang, Zhilong; Xiang, Guifu
Abstract : The Luchedu rock avalanche (LRA) that occurred in 1935 at the junction of Sichuan and Yunnan in Southwest China is a disaster chain of the rock slide, debris avalanche, and river blocking induced by heavy rainfall. The rock slide originated from the wedge formed by sheet metamorphic rocks on the fault zone on the left bank of the Jinsha River. After breaking away from the slope, the wedge disintegrated and cracked rapidly, forming debris and causing them to flow in fluidization along a 7.3 km path. After the obvious entrainment process and curve superelevation in the proximal area, the deposition reached 50.5 × 10 6  m 3 in the distal area. The sedimentary structure of clasts has typical stratification characteristics. The types of sedimentary facies include carapace facies, body facies, and mixed facies. Inside the sedimentary structure, dense shear zones, liquefied intercalations, jigsaw structures, and directional arrangement of particles are observed. Through a detailed geological survey and DEM spatial analysis, the avalanche entrainment rate of LRA was determined as 1.2. The morphological fluctuation of basement lithology and gully path plays an important role in the long-distance movement. The rock fragments formed by metamorphic rocks with a primary schistosity structure can effectively reduce the energy loss in the internal shear process and significantly promote the laminar flow movement in the distal region of the avalanche. Therefore, as a giant rock avalanche formed by the evolution of specific metamorphic rocks, LRA results from the combination of macrohydrodynamics and microrock failure properties.